The international investment regime is stronger than you think: Understanding the interplay of diplomatic, insurance and legal approaches for protecting FDI - Geoffrey Gertz (University of Oxford, Global Economic Governance Programme (GEG), 2015)
Today the assets of foreign investors are protected by three distinct yet overlapping pillars: diplomatic pressure applied by the home state; political risk insurance purchased by the investor; and investor-host state legal arbitration. These pillars represent mutually reinforcing approaches to compensating foreign investors for the adverse effects of host state policy. This paper places these three pillars within a unified conceptual framework, and argues that their overlaps and interactions lead to stronger protections for foreign investors than much of the literature commonly assumes. The creation and institutionalization of new forms of protection for foreign investments over the last half-century have not necessarily replaced or substituted old forms of protection, but rather have complemented and added to them. Two brief case studies - of the Cora de Comstar dispute in Cote d'Ivoire and the Dabhol dispute in India - illustrate how the three pillars operate simultaneously and collectively in contemporary investment dispute settlement. The paper's findings hold important implications for both investors and states.
Keywords: 330; Auslandsinvestition; Internationales Investitionsrecht; Internationale Beziehungen; Indien; Elfenbeinküste